Computational Fluid Dynamics Modeling and Experiments of Two-Phase Flows - Van-Tu Nguyen; Hemant J. Sagar (Fluids, 2024)
Two-phase flows are prevalent in natural phenomena, as well as a wide range of marine engineering and industrial applications [...]